Increasing Financial Knowledge in Supporting MSMEs in Kiangroke Village in Supporting the Digital Market - Arifin, Farid; Noor, Julfan Herliansyah; Ainunnisa, Rarassatika (Abdi Masyarakat, 2023)
Globalization era has changing market conditions which have shifted from conventional models involving face-to-face contact to digital markets that can be accessed in the palm of your hand, Micro, Small and Medium Enterprises (MSMEs) in Kiangroke Village face challenges in terms of financial recording. To become a professional businessman, one of the requirements is to have an effective recording system. Therefore, simple and easy to understand financial training is needed specifically for MSMEs in Kiangroke Village. Purphose of this activity is to encourage MSMEs in Kiangroke Village to be able to manage their business administration well, especially in terms of financial reporting. Apart from that, this activity also aims to provide an understanding of the importance of financial records in making business decisions and increase the competitiveness of MSME players in Kiangroke Village. The methods used in this activity are persuasive methods and discussions with partners, which are divided into preparation stages, implementation stages and evaluation stages. This activity ran smoothly and received the attention of micro, small and medium business actors in Kiangroke Village as partners. The modules provided to assist understanding and use have also been used by partners, although they still require gradual assistance so that financial recording and reporting for micro, small and medium enterprises in Kiangroke Village can run well